2016
DOI: 10.1017/s1751731115002128
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses of breast and leg muscles to essential amino acids in broiler chicks

Abstract: The first three essential amino acids (EAA) for broilers including methionine (Met), lysine (Lys) and threonine (Thr) may greatly influence the growth of chick muscles at early stages of life. In order to survey the potential effects of those EAA on growth muscles, a rotatable three-variable central composite design (CCD) was conducted to track the interrelationships of dietary digestible Met (dMet), Lys (dLys) and Thr (dThr) for optimization of processing yields in broiler chicks using response surface method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Chen et al [37] reported that breast muscle contained higher levels of total essential and non-essential amino acids than those of thigh muscle in commercial broilers. It was demonstrated that the growth of breast muscle required higher ideal ratios of digestible methionine and threonine than leg muscle in boilers [38], which indicated the inconsistent responses of breast and leg muscles. Free amino acids usually increase during the postmortem storage of meat due to the action of aminopeptidases and proteases [39].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [37] reported that breast muscle contained higher levels of total essential and non-essential amino acids than those of thigh muscle in commercial broilers. It was demonstrated that the growth of breast muscle required higher ideal ratios of digestible methionine and threonine than leg muscle in boilers [38], which indicated the inconsistent responses of breast and leg muscles. Free amino acids usually increase during the postmortem storage of meat due to the action of aminopeptidases and proteases [39].…”
Section: Discussionmentioning
confidence: 99%
“…Each model consisted of linear or non-linear parameters (compartments) that could be converged to make a mathematical equation relating the nutrient doses with animal responses. In general, the biological models follow the non-linear manner that has been illustrated in different platforms, including broken lines [ [9] , [10] , [11] , 28 , 29 ], response surface methodology [ [30] , [31] , [32] ], uniform design [ 33 ], artificial neural networks [ 34 , 35 ], and three or four-parameter models [ 36 ] by researchers. The other methods used to estimate the amino acid requirements in monogastric animals are the non-linear logistic and saturation kinetic models [ 37 , 38 ], Rayleigh [ 36 ], and exponential models [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, Gerham et al [ 49 ] described an improved amino acid digestibility in swine by the addition of FSBM to their diets. The increase in breast muscle amino acids may have resulted from its response to higher availability, digestion and absorption of these amino acids in feed, which improved due to the fermentation processes [ 64 ]. Regarding the serum metabolites, replacing soybean meal with DFSBM did not affect liver and kidney function markers, while serum lipid profile was improved through decreasing cholesterol and TAG and elevation of HDL-C concentration.…”
Section: Discussionmentioning
confidence: 99%